iPad fully loaded - Hess, Alan (Wiley Publishing, 2011)
Provides tips and techniques you need to get the absolute most out of your iPad. This title helps to: browse through the iBooksStore and start speed e-reading; catch all the news from traditional sources and news aggregator apps like Pulse and Flipboard; and, get all your photos exactly where - and how - you want them to be